Karakter Pendidikan Islam Masa Klasik dan Modern - Muhammad Yahdi; Andi Achruh; Apriyani, Apriyani (AIJER: Algazali International Journal Of Educational Research, 2024)
Abstract: This research aims to examine the characteristics of Islamic education in the classical and modern periods, as well as the potential for collaboration between classical educational traditions and modern educational methods. The method used in this research is descriptive analysis by reviewing related literature and historical sources. The data analyzed includes the characteristics of education during the time of the Prophet Muhammad, Khulafaur Rasyidin, Bani Umayyah, Abbasids, as well as the modern era. The conclusion shows that Islamic education in the classical period emphasized memorizing sacred texts, moral development, and discussion-based learning. Meanwhile, in modern times, there is an integration of modern science, the use of technology, and a multicultural approach in the curriculum. Collaboration between classical traditions and modern methods can enrich the Islamic education system, ensuring its relevance and effectiveness in the era of globalization.